Rapid mini-chromosome divergence among fungal isolates causing wheat blast outbreaks in Bangladesh and Zambia - Liu, Sanzhen; Lin, Guifang; Ramachandran, Sowmya R.; Calderon Daza, Lidia; Cruppe, Giovana; Tembo, Batiseba; Singh, Pawan Kumar; Cook, David; Pedley, Kerry F.; Valent, Barbara (Wiley, 2024)
The fungal pathogen, Magnaporthe oryzae Triticum pathotype, causing wheat blast disease was first identified in South America and recently spread across continents to South Asia and Africa. Here, we studied the genetic relationship among isolates found on the three continents. Magnaporthe oryzae strains closely related to a South American field isolate B71 were found to have caused the wheat blast outbreaks in South Asia and Africa. Genomic variation among isolates from the three continents was examined using an improved B71 reference genome and whole-genome sequences. We found strong evidence to support that the outbreaks in Bangladesh and Zambia were caused by the introductions of genetically separated isolates, although they were all close to B71 and, therefore, collectively referred to as the B71 branch. In addition, B71 branch strains carried at least one supernumerary mini-chromosome. Genome assembly of a Zambian strain revealed that its mini-chromosome was similar to the B71 mini-chromosome but with a high level of structural variation. Our findings show that while core genomes of the multiple introductions are highly similar, the mini-chromosomes have undergone marked diversification. The maintenance of the mini-chromosome and rapid genomic changes suggest the mini-chromosomes may serve important virulence or niche adaptation roles under diverse environmental conditions.